Research on the Innovative Application of Bamboo in Modern Product Design with the Aid of Computer Simulation Software. Issue 2 (October 2020) - Lu, Libo
Abstract: In view of the problems existing in the development of bamboo products in China, several innovative design methods of bamboo products are proposed from the perspective of modern design, including the use of modern styling concepts, modern design concepts, and modern manufacturing techniques. Therefore, under the circumstance of this change of ideas, the ecological value, human value and economic value of bamboo products have been re-excavated. The intrinsic meaning of bamboo is consistent with the ideas of many people, and the bamboo industry has also become the origin of bamboo in China. It provides some references for the design innovation of bamboo products in the future. Based on this, this paper uses computer simulation software to assist in the research on the innovative application of bamboo in modern product design.